Promoção da saúde mental de graduandos da UFPB: proposições para uma atuação institucional - Gouveia, Mirtila Marina Wood (2020)
This technical report aimed to develop proposals for institutional action concerning the promotion of mental health of undergraduate students at the Federal University of Paraíba (UFPB), based on contributions from experiences of other higher education institutions and from Course Coordinators of UFPB. Mental health problems have been a topic of concern, raising discussions that point to the need for interventions within the institutional reality. It becomes evident that the issue transcends the health sector and urgently needs to be a priority agenda for the university management. Starting from the settings-based approach to health promotion as a strategy for the university context, this report performs qualitative research, collecting data through systematic literature review and application of questionnaire and focus group interview with Course Coordinators, to gather and build perspectives for institutional action. Categorical content analysis (AC) underlies this interpretation. From the experience of other institutions, some reference elements stand out: incorporating health into the processes and decision making, community engagement, leadership commitment, use of institutional and educational resources and tools, development of competencies and partnerships, work from evidence, among others. From the coordinators standpoint, it was verified the activities accomplished within the scope of the Courses, the experiences and difficulties for the managers, some recommendations brought by them, as well as factors that they consider relevant for the institutionalization of action. As a final product, proposals are forwarded for an institutional action by the UFPB to the promotion of student mental health. Thus, it is expected to contribute with reflections on the possibilities of intervention in promoting mental health in higher education, as well as adding subsidies for health promotion practices in the work of managers and staff at UFPB. Perhaps, still, to serve as a tool of use by catalyst agents for a mobilization in favor of the settings-based approach within the institution.